VD_FINDINFO HC / 2021 / 723 vom 15. Oktober 2021 - VD Tribunal cantonal (2021)
OBLIGATION D'ENTRETIEN, ENFANT, REVENU HYPOTHÉTIQUE, PROTECTION DE L'UNION CONJUGALE | 176 al. 1 CC, 176 al. 3 CC, 285 CC